Aerobic Aliphatic Hydroxylation Reactions by Copper Complexes: A Simple Clip‐and‐Cleave Concept. Issue 58 (4th September 2018) - Becker, Jonathan; Zhyhadlo, Yevheniia Y.; Butova, Ekaterina D.; Fokin, Andrey A.; Schreiner, Peter R.; Förster, Moritz; Holthausen, Max C.; Specht, Pascal; Schindler, Siegfried
Abstract: A simple imine clip‐and‐cleave concept has been developed for the selective hydroxylation of non‐activated CH bonds in aliphatic aldehydes with dioxygen through a copper complex. The synthetic protocol involves reaction of a substrate aldehyde with N, N ‐diethyl‐ethylendiamine to give the corresponding imine, which is used as a bidentate donor ligand forming a copper(I) complex with [Cu(CH3 CN)4 ][CF3 SO3 ]. After exposure of the reaction mixture to dioxygen acidic cleavage and aqueous workup liberates the corresponding β‐hydroxylated aldehyde. The concept for the hydroxylation of trimethylacetaldehyde as well as adamantane and diamantane 1‐carbaldehydes was investigated and the corresponding β‐hydroxy aldehydes were obtained with high selectivities. The results of low temperature stopped‐flow measurements indicate the formation of a bis( μ ‐oxido)dicopper complex as reactive intermediate. According to density functional theory (DFT, RI‐BLYP‐D3/def2‐TZVP(SDD)/ COSMO(CH2 Cl2 )//RI‐PBE‐D3/def2‐TZVP(SDD)) computations CH bonds suitably predisposed to the [Cu2 O2 ] 2+ core undergo hydroxylation in a concerted step with particularly low activation barriers, which explains the experimentally observed regioselectivities. Abstract : Getting selective : A simple imine clip‐and‐cleave system has been developed for the selective hydroxylation of aldehydes with dioxygen through a copper complex.